Magnetic anisotropy and slow magnetic relaxation processes of cobalt(ii)-pseudohalide complexes. Issue 28 (28th June 2019) - Cui, Hui-Hui; Zhang, Yi-Quan; Chen, Xue-Tai; Wang, Zhenxing; Xue, Zi-Ling
Abstract : Magnetic measurements, HFEPR and ab initio calculations were used to study the magnetic anisotropies and magnetic relaxation of four cobalt(ii )-pseudohalide complexes. Abstract : Three mononuclear six-coordinate Co(ii )-pseudohalide complexes [Co(L)X2 ] with two N-donor pseudohalido coligands occupying the cis -positions (X = NCS − (1 ), NCSe − (2 ) or N(CN)2 − (3 )), and a five-coordinate complex [Co(L)(NCO)][B(C6 H5 )4 ] (4 ) [L = 1, 4, 7, 10-tetramethyl-1, 4, 7, 10-tetraazacyclododecane (12-TMC)] have been prepared and structurally characterized. Easy-plane magnetic anisotropy for1–3 and easy-axis anisotropy for4 were revealed via the analyses of the direct-current magnetic data, high-frequency and -field EPR (HFEPR) spectra and ab initio theoretical calculations. They display slow magnetic relaxations under an external applied dc field. Typically, two slow relaxation processes were found in1 and2 while only one relaxation process occurs in3 and4 . The Raman-like mechanism is found to be dominant in the studied temperature range in1 . For2–4, the Raman process is dominant in the low temperature region, while the Orbach mechanism dominates in the high temperature range.